Ln3+:YAG obtained via spray pyrolysis - particles and fibroinbased compounds, and its photonic applications - Pugina, Roberta Silva (2022)
Advances in photonics are related to obtaining new materials and nanostructured systems, as well as studying non-linear effects. In this sense, laser emission resulting from the confinement of light in a disordered structure is a promising field of research, as well as the development of optical thermometers and materials that can be applied as anti-counterfeiting devices, among others. In this work, YAG (Yttrium Aluminum Garnet, Y3Al5O12) spheres doped with different lanthanide ions were obtained via spray pyrolysis, a methodology that provides high yield and can be used for large-scale production, without generating byproducts, and offering the advantage of not introducing impurities into the final product, since there is no external contact with the precursors, and each drop constitutes a homogeneous mini reactor that has the same chemical composition as the initial solution. During the synthesis and even after heat treatment at 1100 °C, the particles did not coalesce. All characterizations confirmed that the YAG phase was obtained in the presence of lanthanide ions (Nd3+, Yb3+/Er3+ or Yb3+/Tm3+), which had their spectroscopic properties analyzed and explored for photonic applications. The Nd3+:YAG particles were studied for their emissions in disordered environments, Yb3+/Er3+:YAG were intended for studies at different temperatures, while in the Yb3+/Tm3+:YAG systems the characteristic blue-emission was observed, which makes this material a possible candidate for an anti-counterfeiting device. Furthermore, aiming for biological applications, these particles were added to silk fibroin which is a biocompatible matrix that allows the insertion of different ions, molecules or nanoparticles; that shows good suitability in optical systems, mainly due to high transparency (> 95%) throughout the visible region of the spectrum; that is mechanically robust and moldable in the form of films, wires and particles. In the case of SF-Yb3+/Er3+:YAG and SF-Yb3+/Tm3+:YAG composites, the same behavior observed in the particles was also observed in the film form.